Detail Engineering Desain (DED) Air Minum di Desa Amdasa Kecamatan Wertamrian Kabupaten Maluku Tenggara - Wattimena, Linda Euaggelion; Frans, Pieter Lourens; Betaubun, Renny James (JURNAL ILMIAH NUSANTARA, 2025)
The availability of clean water is a very important basic need for the community, especially in rural areas such as Amdasa Village, Wertamrian District, Southeast Maluku Regency. However, limited infrastructure and inadequate water distribution systems are the main obstacles in meeting the clean water needs of the local community. The provision of clean and sustainable drinking water is a basic need for the community, especially in remote areas such as Amdasa Village, Wertamrian District, Southeast Maluku Regency. This study aims to compile a Detail Engineering Design (DED) for a drinking water supply system that is in accordance with the geographical conditions and needs of the local community. The research methods include field surveys, water needs analysis, and design of distribution systems and water treatment installations. The results of this study are expected to be the basis for planning the development of efficient and sustainable drinking water infrastructure in Amdasa Village.